Reference ranges of oxidative stress biomarkers selected for non-invasive biological surveillance of nanotechnology workers: Study protocol and meta-analysis results for 8-OHdG in exhaled breath condensate. (1st July 2020) - Hemmendinger, M.; Wild, P.; Shoman, Y.; Graille, M.; Bergamaschi, E.; Hopf, N.; Guseva Canu, I.
Highlights: A systematic review and meta-analysis were conducted to determine the reference range of 8-OHdG in the EBC. The null hypothesis that the 8-OHdG levels in EBC are consistent across the different control groups was strongly rejected. Between-study variability was very high; mainly confounded by the analytical method and completely dominated the within-studies variability. Smoking was evidenced as a potential determinant of 8-OHdG inter-individual variability but only when immunochemical analysis was used. Estimated reference values should be considered preliminary; based on a limited number of studies, mostly of moderate to low quality of evidence. Abstract: In the field of engineered nanomaterials (ENMs) and other airborne particulate exposure biomonitoring, circulating oxidative stress biomarkers appear promising. These biomarkers could be monitored in different biological matrices. Exhaled breath condensate (EBC) enables their measurements in the respiratory tract, without affecting airway function or creating inflammation. The 8-hydroxy-2-deoxyguanosine (8-OHdG) was found increased in the EBC of ENM-exposed workers. Our objectives were to assess the reference range of 8-OHdG in the EBC and to identify determinants of its inter- and intra-individual variability. The meta-analysis was stratified by analytical method (chemical versus immunochemical analysis) and resulted in a between-study variability over 99 % of the total variability. The between-study variability completely dominated the within-studies variability. By using a mixed model with study ID as a random effect rather than a meta-regression, only smoking was evidenced as a potential determinant of 8-OHdG inter-individual variability, and only when immunochemical analysis was used. To our knowledge, this is the first meta-analysis aimed at estimating reference values for 8-OHdG in the EBC. The estimated values should be considered preliminary, as they are based on a limited number of studies, mostly of moderate to low quality of evidence. Further research is necessary to standardize EBC sampling, storage and analytical methods. Such a standardization would enable a more accurate estimation of the reference ranges of the 8-OHdG and potentially other biomarkers measurable in the EBC, which are essential for a meaningful interpretation of the biomonitoring results.